Algebraic method for independence model of two-way contingency tables - Mohammed, Nadia Faiq; Rakhimov, Isamiddin Sattarovich; Shitan, Mahendran (Institute for Mathematical Research, Universiti Putra Malaysia, 2017)
The main purpose of the study is to propose an algebraic method to obtain the set of all independence models of I×J two-way contingency tables with the same row sums and column sums which is called fiber in algebraic statistics. This method involves solving a system of linear algebraic equations that only rely on row sums and column sums of the I×J two-way contingency table. The MATLAB software was used to solve this system. The effectiveness of the purposed method is illustrated by applying to a contingency table of agriculture teachers’ perception of secondary school agriculture.